A Study of Menstrual Hygiene Among Adolescent School Girls in A Slum Area of Kolkata - Madhumita Bhattacharyya; Papia Sen; Suprakash Hazra; Rabindra Nath Sinha; Sanjoya Sahoo (Medsci Publications, 2015)
Introduction: Reproductive tract infections are common among the adolescent girls. Poor menstrual and personal hygiene are known contributory factors. Objectives were to examine the prac- tice of menstrual hygiene among the adolescent school girls of ur- ban slum area and to see the association between use of sanitary napkin and prevalence of Leucorrhoea with low back pain or ab- dominal pain and vaginal burning/itching among them. Methods: A cross sectional observational study was carried out among 460 adolescent girl students of an urban slum area with a predesigned, pretested questionnaire based on Global School - based Student Health survey. Data were analyzed using SPSS, ver- sion 21. Results: Among 460 girls, 275 (60%) girls were from low socioeco- nomic status. Out of 376 (81.73%) girls who used only sanitary nap- kin, 359 (94.14%) girls did not complain of symptomatic leucor- rhoea and 326 (87.70%) had no vaginal itch or burning. Sixty eight (80.95%) and 62 (73.80%) girls out of 84 girls who did not use only sanitary napkin had symptomatic leucorrhoea. (P<0.000, OR 68.38) and had vaginal itch/burning (P<0.000, OR 18.37) respectively. Conclusion: Use of sanitary napkin is highly prevalent among the adolescent girls from slum and incidence of symptomatic leucor- rhoea and vaginal itch/burning was significantly less among sani- tary napkin users.